The Relationship between Cognitive Function and the Ability of Social Interaction in the Elderly in Gresik - Nasir, Abd.; Rindayati, Rindayati; Yusuf, Ah; Haryanto, Joni; Iswatun, Iswatun (International Journal of Psychosocial Rehabilitation, 2020)
Cognitive impairment analysis that is associated with social interaction problems is important in order to know whether the intellectual ability of the elderly influences social activities carried out daily. The aim of the study was to identify cognitive functions and their relation to the ability of social interaction in the elderly. A cross-sectional study was conducted from 1 February to 30 May 2019, among the elderly in Gresik District. The sample selected as many as 102 respondents. The sampling technique used proportional random sampling. The independent variable is the cognitive function. The dependent variable is the ability of social interaction. The statistical test used is the Phi Coefficient test which showed a significant relationship between cognitive function and social interaction abilities in the elderly with the value (X 2 ) count of 75.683 and Phi coefficient ( φ) value of 0861, p = 0.000. The elderly need an environment that supports social interaction to avoid cognitive decline so they need facilities that can be used to interact and communicate with fellow elderly people.